2015
DOI: 10.1016/j.watres.2014.12.018
|View full text |Cite
|
Sign up to set email alerts
|

Relating methanogen community structure and anaerobic digester function

Abstract: Abstract:Much remains unknown about the relationships between microbial community structure and anaerobic digester function. However, knowledge of links between community structure and function, such as specific methanogenic activity (SMA) and COD removal rate, are valuable to improve anaerobic bioprocesses. In this work, quantitative structure-activity relationships (QSARs) were developed using multiple linear regression (MLR) to predict SMA using methanogen community structure descriptors for 49 cultures. Co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 53 publications
0
22
0
Order By: Relevance
“…A possible approach is the one suggested by Bocher et al . () in which enrichment cultures were used in combination with denaturing gradient gel electrophoresis and mcrA gene analysis for specific methanogenic activity prediction. Given the increasing availability of microbial community composition data in AD via high‐throughput amplicon sequencing and omics methods, this concept can be expanded to develop a suitable prediction strategy.…”
Section: Community Composition Stability Prediction Indicator (Coco‐smentioning
confidence: 99%
“…A possible approach is the one suggested by Bocher et al . () in which enrichment cultures were used in combination with denaturing gradient gel electrophoresis and mcrA gene analysis for specific methanogenic activity prediction. Given the increasing availability of microbial community composition data in AD via high‐throughput amplicon sequencing and omics methods, this concept can be expanded to develop a suitable prediction strategy.…”
Section: Community Composition Stability Prediction Indicator (Coco‐smentioning
confidence: 99%
“…Produced biogas was then removed and substrate (either acetate or H2/CO2) was added. SMA using acetate was performed for 40 days as described by Bocher et al (2015) using biomass concentration of 1.5 to 1.8 g VS/L and 10 g/L calcium acetate at 10 °C. For SMA using H2/CO2, biomass concentration was 0.2 g VS/L and serum bottle headspace was charged with 100 mL of a 4:1 mixture of H2/CO2 gas that had been previously cooled to 10 °C.…”
Section: Methanogenic Activitymentioning
confidence: 99%
“…A high evenness score indicates unique community members are evenly distributed, which is beneficial for functional redundancy (Fernandez et al, 2000). Additionally, ordination techniques including nonmetric multi-dimensional scaling (NMDS) and principal component analysis (PCA) have been useful to compare microbial community differences in separate systems (Bialek et al, 2011 andBocher et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…Methanogens possess an operon that encodes the methyl coenzyme M reductase (MCR). The presence and transcription of the gene that encodes the alpha subunit of MCR (mcrA) has been used to detect methanogen presence and activity in the environment (Springer et al 1995;Luton et al 2002;Juottonen et al 2008;Steinberg and Regan 2009;Kampmann et al 2012;Zeleke et al 2013;Bocher et al 2015). Previously, we showed that mcrA gene copy numbers, but not transcript numbers, positively correlated with SMA values in laboratory methanogenic enrichments (Morris et al 2014).…”
Section: Introductionmentioning
confidence: 96%
“…; Bocher et al . ). Previously, we showed that mcrA gene copy numbers, but not transcript numbers, positively correlated with SMA values in laboratory methanogenic enrichments (Morris et al .…”
Section: Introductionmentioning
confidence: 97%